Nonviolence and Peace Psychology - Mayton, Daniel; SpringerLink (Online service) (New York, NY : Springer US, 2009)
Recent trends and events worldwide have increased public interest in nonviolence, pacifism, and peace psychology as well as professional interest across the social sciences. Nonviolence and Peace Psychology assembles multiple perspectives to create a more comprehensive and nuanced understanding of the concepts and phenomena of nonviolence than is usually seen on the subject. Through this diverse literature-spanning psychology, political science, religious studies, anthropology, and sociology-peace psychologist Dan Mayton gives readers the opportunity to view nonviolence as a body of principles, a system of pragmatics, and a strategy for social change. This important volume: Draws critical distinctions between nonviolence, pacifism, and related concepts. Classifies nonviolence in terms of its scope (intrapersonal, interpersonal, societal, global) and pacifism according to political and situational dimensions. Applies standard psychological concepts such as beliefs, motives, dispositions, and values to define nonviolent actions and behaviors. Brings sociohistorical and cross-cultural context to peace psychology. Analyzes a century's worth of nonviolent social action, from the pathbreaking work of Gandhi and King to the Courage to Refuse movement within the Israeli armed forces. Reviews methodological and measurement issues in nonviolence research, and suggests areas for future study. Although more attention is traditionally devoted to violence and aggression within the social sciences, Nonviolence and Peace Psychology reveals a robust knowledge base and a framework for peacebuilding work, granting peace psychologists, activists, and mediators new possibilities for the transformative power of nonviolence
Meaning of Nonviolence and Pacifism -- Recent History of Nonviolent Responses to Conflict -- Theories of Nonviolence -- Intrapersonal Perspectives of Nonviolence -- Interpersonal Perspectives of Nonviolence -- Cultural and Societal Perspectives of Nonviolence -- Nonviolent Perspectives Within the Abrahamic Religions -- Situational Influences on Nonviolent Action -- Measurement Tools for Research on Nonviolence and Related Concepts -- New Directions for Research on Nonviolence.
Keywords: PHILOSOPHY (GENERAL).; APPLIED PSYCHOLOGY; PSYCHOLOGY; CROSS CULTURAL PSYCHOLOGY; SOCIOLOGY, GENERAL